(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Composite materials are materials that consist of two or more components (phases). The first modern composite material - engineer A.K. Burov was discovered in the late 1930s. For several decades after the end of World War II, the direction associated with the development and use of composite materials in the fields of science and technology developed very intensively